(untitled) (Baghdad Science Journal, 2025)
General survey for wheat rust diseases in Iraqi fields was done during the seasons of 2010, 2011 and 2012. The survey covered different fields in southern, middle and northern regions. Results of the first season indicated that most of Iraqi cultivars such as Tmmoze2, IPA 99 and Mexipak showed different types of susceptibility to both yellow and leaf rust infection. Disease severity increased when the conditions were favorable for infections with using susceptible cultivars. The severity of leaf rust was less in the north region comparing with the middle and south regions. Most of the introduced cultivars such as Sham6 and Cimmyto showed susceptible reaction to yellow and leaf rust. Yellow rust was in epiphytotic form at the Iraqi-Syrian-Turkish triangle where the disease severity was 100%. Low disease severity of stem rust was observed on some cultivars (1-5%), except for the cultivar Mexipak which showed 40%S in Najaf. Rusts at season of 2011 were restricted mostly in Baghdad and the yellow rust was dominant. The AUDPC of 15 wheat cultivars showed that Sawa and Sali were highly susceptible to the three types of rusts while Babil113 and Tamoze2 were resistant. No rusts were detected at season 2012.